2019
DOI: 10.1002/ijc.32232
|View full text |Cite
|
Sign up to set email alerts
|

Trends in cause of death among patients with multiple myeloma in Puerto Rico and the United States SEER population, 1987–2013

Abstract: Multiple myeloma (MM) survival has improved due to recent developments in MM treatment. As a result, other co‐morbid conditions may be of increasing importance to MM patients’ long‐term survival. This study examines trends in common causes of death among patients with MM in Puerto Rico, and in the US Surveillance, Epidemiology, and End Results (SEER) population. We analyzed the primary cause of death among incident MM cases recorded in the Puerto Rico Central Cancer Registry (n = 3,018) and the US SEER Program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…A recent study showed that, myeloma caused 71.3% of deaths in SEER database and 71.7% in the database of the Puerto Rico Central Cancer Registry, among MM patients aged more than 40 between 1987 and 2013. [ 25 ] In our study, it was similar that 74.89% of deaths in MM patients were attributed to myeloma, but it was the second ranking cause of death in pPCL, which caused only 38.83% of deaths. Interestingly, 31.13% of pPCL patients who died of myeloma occurred in the first 6 months after diagnosis, however, the proportion was only 17.23% in MM.…”
Section: Discussionsupporting
confidence: 75%
“…A recent study showed that, myeloma caused 71.3% of deaths in SEER database and 71.7% in the database of the Puerto Rico Central Cancer Registry, among MM patients aged more than 40 between 1987 and 2013. [ 25 ] In our study, it was similar that 74.89% of deaths in MM patients were attributed to myeloma, but it was the second ranking cause of death in pPCL, which caused only 38.83% of deaths. Interestingly, 31.13% of pPCL patients who died of myeloma occurred in the first 6 months after diagnosis, however, the proportion was only 17.23% in MM.…”
Section: Discussionsupporting
confidence: 75%
“…The translational relevance of identifying these high-risk IgA PCM could be significant for PCM patients, especially in Puerto Rico. Although PCM survival has improved due to new treatment modalities, the majority (~72%) of Puerto Ricans diagnosed with PCM are still likely to die from PCM [ 18 ]. Also, for unknown reasons, the decline in PCM-specific mortality in Puerto Rico is less than in other comparable US populations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable advances in the treatment of multiple myeloma (MM) in recent decades, MM remains an incurable malignancy, associated with significant morbidity and mortality 1–4 . Therapeutic and supportive measures that reduce disease‐related complications and increase duration until disease progression are essential to improve the management of MM 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite considerable advances in the treatment of multiple myeloma (MM) in recent decades, MM remains an incurable malignancy, associated with significant morbidity and mortality. [1][2][3][4] Therapeutic and supportive measures that reduce disease-related complications and increase duration until disease progression are essential to improve the management of MM. 2 Patients have greater access to such measures at the Commission on Cancer (CoC) accredited academic cancer centers (ACs), which are defined by the availability of MM specialists, access to comprehensive cancer treatment, and high patient volume, which has previously been shown to be independently associated with improved survival in MM.…”
Section: Introductionmentioning
confidence: 99%